2019
DOI: 10.1038/s41598-019-51966-4
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the depth of pre-instrumental earthquakes from macroseismic intensity data: a case-history from Northern Italy

Abstract: Determining the hypocentral depth of pre-instrumental earthquakes is a long-standing geophysical issue that still awaits to be elucidated. Using very well documented recent earthquakes we found that the depth of crustal and upper-mantle events correlates well with the slope of the first 50 km of their intensity attenuation curve, regardless of their magnitude. We used this observation to build a magnitude-independent method for calculating the depth of selected historical and early-instrumental earthquakes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 50 publications
3
40
0
Order By: Relevance
“…Many geothermal fields occur in tectonically-active regions and maps of active faults have been used both for exploration and selection of drilling sites 15 , 16 as well as for reservoir modelling during exploitation 17 , 18 . Active fault databases have been also used in studies of volcanotectonic interactions and structural control on volcanism in rifts 19 and arcs 20 , in the interpretation of present-day stress indicators 21 , 22 as well as to infer sources of pre-instrumental earthquakes 23 and the response of groundwater to near and farfield earthquakes 24 . Analyses of the rupture mechanism, propagation and kinematics of many recent earthquakes and earthquake sequences have relied on databases of active faults derived from geomorphic and geologic data to interpret subsurface observations and develop conceptual models 3 , 6 , 25 , 26 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Many geothermal fields occur in tectonically-active regions and maps of active faults have been used both for exploration and selection of drilling sites 15 , 16 as well as for reservoir modelling during exploitation 17 , 18 . Active fault databases have been also used in studies of volcanotectonic interactions and structural control on volcanism in rifts 19 and arcs 20 , in the interpretation of present-day stress indicators 21 , 22 as well as to infer sources of pre-instrumental earthquakes 23 and the response of groundwater to near and farfield earthquakes 24 . Analyses of the rupture mechanism, propagation and kinematics of many recent earthquakes and earthquake sequences have relied on databases of active faults derived from geomorphic and geologic data to interpret subsurface observations and develop conceptual models 3 , 6 , 25 , 26 .…”
Section: Background and Summarymentioning
confidence: 99%
“…In particular, the 1909 earthquake had a macroseismic epicentre located south of Ferrara and affected a very large area with slight to moderate damages (Rovida et al, 2021). This macroseismic scenario was interpreted as being caused by the significant depth of the event (Meloni and Molin, 1987;Faccioli, 2013;Vannoli et al, 2015), and, as suggested by Sbarra et al (2019), it may have occurred well below the basal detachment of the northern Apennines outer fronts at a depth of 41 km, with a recalculated M w of 6.2.…”
Section: Seismotectonic Evidencementioning
confidence: 98%
“…They extended the research to the conterminous Veneto region, which belonged to Italy during the Habsburg Monarchy (1804-1867) and the Austro-Hungarian Empire . It has been suspected that these geologists were also military officers with the purpose of knowing the border territories (Scalia, 1917). In fact, although they reported thorough publications on the stratigraphy, palaeontology and tectonics of the Italian territories lying at the southern Austrian border, their geological maps never represented the Austrian side.…”
mentioning
confidence: 99%
“…Inferring focal depths from macroseismic data provides a robust and alternative way if instrumental data is lacking (Sbarra et al, 2019). Previous authors used intensity data to evaluate the focal depth of some of the largest earthquakes in Hainaut.…”
Section: Focal Depth Determinationmentioning
confidence: 99%